2018
DOI: 10.3390/insects9030110
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality during Development Alters Insulin-Like Peptides’ Expression and Physiology of the Adult Yellow Fever Mosquito, Aedes aegypti

Abstract: Mosquitoes have distinct developmental and adult life history, and the vectorial capacity of females has been shown to be affected by the larval nutritional environment. However, little is known about the effect of developmental nutrition on insulin-signaling and nutrient storage. In this study, we used Aedes aegypti, the yellow fever mosquito, to determine whether larval nutrition affects insulin gene expression. We also determined the traits regulated by insulin signaling, such as stored-nutrient levels and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The hatchability of Plutella xylostella offspring decreased by 20% when adults experienced natural high temperature for 1 d [41]. This phenomenon was also observed in Grapholitha molesta [36]. However, our study found that there was no significant effect on the oviposition amount and egg hatching rate for adults resulting from high-temperature-stressed larvae ( Figure 5A,B), which suggests that high-temperature stress only affected the contemporary growth and development of B. odoriphaga and had no effect on offspring.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The hatchability of Plutella xylostella offspring decreased by 20% when adults experienced natural high temperature for 1 d [41]. This phenomenon was also observed in Grapholitha molesta [36]. However, our study found that there was no significant effect on the oviposition amount and egg hatching rate for adults resulting from high-temperature-stressed larvae ( Figure 5A,B), which suggests that high-temperature stress only affected the contemporary growth and development of B. odoriphaga and had no effect on offspring.…”
Section: Discussionsupporting
confidence: 59%
“…The longevity of male and female adults depends on the insect species [36] and its reproductive characteristics [37]. Since living requires energy consumption, insects can extend their lifespan by obtaining energy from nature [38].…”
Section: Discussionmentioning
confidence: 99%
“…Eggs were hatched overnight in small plastic cups with deionized water. First instar larvae were counted (150 per pan) and reared in 500 ml of deionized water on a powdered fish food diet (Tetramin ® , Melle, Germany) as described in detail by Pooraiiouby et al 30 . Pupae were collected from rearing pans and were transferred to adult emergence cages.…”
Section: Methodsmentioning
confidence: 99%
“…Two mosquitoes per sample were collected in triplicate at each time point per treatment. Samples were processed for micro-separation of metabolites from both males and females according to previously established protocols 30 . Levels of trehalose and glycogen were estimated using the anthrone assay and lipids were measured with a vanillin assay 29 .…”
Section: Survival Assaysmentioning
confidence: 99%
See 1 more Smart Citation